VO#043 Quotation for components material cost in internal electrification works rev.01 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of revised price quotation for components material cost in internal electrification works of BRACU new campus project.